AB0120 Elevated LYSYL hydroxylase 2B expression and pyridinoline cross-link formation in collagenase-induced OA; the cause of OA-related fibrosis?. (23rd January 2014) - Remst, D.F.; Blaney Davidson, E.N.; Vitters, E.L.; Blom, A.B.; Stoop, R.; Snabel, J.M.; Bank, R.A.; van den Berg, W.B.; van der Kraan, P.M.
Abstract : Background: Fibrosis is a major contributor to joint stiffness in osteoarthritis (OA) and associated with joint pain. In different fibrotic diseases there is an increase in the number of pyridinoline cross-links, resulting in harder to degrade collagen. Lysyl hydroxylase 2b (LH2b) is the enzyme responsible for pyridinoline cross-link formation. Objectives: We examined whether LH2b expression and the number of pyridinoline cross-links per triple helix collagen was elevated in the synovium of mice with collagenase-induced OA. In addition, to elucidate the mechanisms by which LH2b is induced and how to prevent its induction, we investigated whether TGF-β-induced LH2b was Smad2P or Smad3P dependent. Methods: We induced OA by intra articular injection of collagenase into the right knee joint of C57Bl/6 mice. Mice were sacrificed at day 7, 21, 28 and 42 after collagenase injection and the mRNA was isolated from the synovium for Q-PCR analysis. Paraffin sections of the murine joints were stained immunohistochemically for LH2 to determine the LH2 expression. The number of pyridinoline cross-links per triple helix in synovium was determined with HPCL. All animal experiments were approved by the local animal ethics committee. Human fibroblasts (hSF) were isolated from synovial tissue of knee joints of OA patients undergoing arthroplasty. The hSF were stimulated with TGF-β alone or in combination with the Smad3P inhibitor SIS3 or the ALK5 kinase inhibitor SB-505124 (SB-5). RNA was isolated and the gene expression for LH2b and collagen type 1 (Col1a1) were analyzed with Q-PCR. Results: On al measured time points LH2b mRNA expression was significantly upregulated in the synovium of OA-affected knee joints compared to the healthy joints. Histological sections of murine knee joints with collagenase-induced OA showed a mild increase in the thickness of the synovial membrane at day 7 whereas a large increase was seen on later days. Day 7 showed a strong increase in LH2 staining, at later time points there was still a clear increase but less intense than at day 7. There was a significant increase in the number of pyridinoline cross-links per triple helix after day 7 compared to control knee joints. TGF-β upregulated both LH2b and Col1A1 gene expression in hSF. The Smad3P inhibitor SIS3 strongly down-regulated Col1A1 in both the presence as absence of TGF-β. In contrast to Col1a1, LH2b was still induced by TGF-β in the presence of SIS3. SB-5 blocked both TGF-β-induced LH2b and Col1a1. Conclusions: We show a strong upregulation of LH2(b) expression and more than a doubling in pyridinoline cross-links per triple helix in the synovium of murine knee joints with collagenase-induced OA. TGF-β, that is elevated during OA, is most likely the driving force of enhanced LH2b expression. We showed previously that TGF-β-induced LH2b relies on ALK5 (Smad2/3) and not ALK1 signaling. Blocking both Smad2 and Smad3 signaling prevented TGF-β-induced LH2b, whereas LH2b was still induced by TGF-β when only Smad3P was inhibited. This suggests that LH2b is mediated through ALK5/Smad2P. We propose that LH2b is responsible for the persistence of fibrosis during OA. Blocking LH2b, or the Smad2P route, in OA may therefore prevent the formation of fibrosis. Disclosure of Interest: None Declared